Economic Model for Assessing the Return on Investments in Structural Health Monitoring Systems - V. Devyatov, Ivan; A. Iurgenson, Sergei; A. Zharenov, Ivan; A. Trutnenko, Andrei; V. Tuev, Dmitrii (International Journal of Criminology and Sociology, 2022)
urpose: The purpose of this article is the description of the approach to the economic assessment of a highly-effective system for state monitoring of structures ensuring an increase in safety and economic efficiency for utilization of complex engineering structures and buildings considering all existing risks. Design/Methodology/Approach: The essence of the approach is in obtaining the state control data of these structures and buildings from sensors, which detect hidden damages and cracks, monitor consequences of shocks, corrosion, tension, and overheating. Findings: All the collected data make up the predictive analysis using artificial intelligence, which can and must analyze this data in real-time mode. Practical Implications: Such a way for monitoring allows for assessing the state of the structures and repairing or replacing them before the critical moments occur, thus significantly reducing the cost of servicing data from complex engineering objects, as well as it ensures their reliability and safety. Digitalization should be introduced in all of the industrial sectors, including aviation, where effectiveness, reliability, and safety are closely interconnected. Originality/Value: Thanks to the development of the state monitoring systems and the economic efficiency of their use in critical structures, the possibility, and intensiveness of their improvement are growing. This has great value and pushes modern productions forward.